If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + 3 = 63 Reorder the terms: 3 + 6n = 63 Solving 3 + 6n = 63 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 6n = 63 + -3 Combine like terms: 3 + -3 = 0 0 + 6n = 63 + -3 6n = 63 + -3 Combine like terms: 63 + -3 = 60 6n = 60 Divide each side by '6'. n = 10 Simplifying n = 10
| 5(3y-1)-1(2y)=10 | | x^2-37=0 | | -5x^2+10x=0 | | -3+n=-91 | | -2x=7y-19 | | -17=63+n | | 2+5*3+4= | | 35x^2+x-6=0 | | n+(-3)=-91 | | 7.32xA=13.53+2.81xA | | 9+2(x-7)=0 | | 2x+(3x+4)=4 | | 92=6+3w | | 92=6+1/2 | | 7x-4=2x+2 | | 92=2+6w | | 0x-.99-3x=-15 | | 92=6+2w | | 2a^2=196 | | 0.4x=8 | | 315=21s | | 15x^2=-3-14x | | 792=-33y | | 24+x^2=10x | | x-2x-1=x+1 | | 0.6+0.3x=0.8+0.4x | | 54+9r-3r^2= | | 54+0r-3r^2= | | 30x-12-3x=-12 | | x^2+5x+11= | | 2w+2(w+20)=380 | | 16z-24=(2z-3) |